Calmodulin kinase modulates Ca(2+) release in mouse skeletal muscle - Tavi, Pasi (Blackwell Science Inc, 2003)
Activation of the contractile machinery in skeletal muscle is initiated by the action-potential-induced release of Ca(2+) from the sarcoplasmic reticulum (SR). Several proteins involved in SR Ca(2+) release are affected by calmodulin kinase II (CaMKII)-induced phosphorylation in vitro, but the effect in the intact cell remains uncertain and is the focus of the present study. CaMKII inhibitory peptide or inactive control peptide was injected into single isolated fast-twitch fibres of mouse flexor digitorum brevis muscles, and the effect on free myoplasmic [Ca(2+)] ([Ca(2+)](i)) and force during different patterns of stimulation was measured. Injection of the inactive control peptide had no effect on any of the parameters measured. Conversely, injection of CaMKII inhibitory peptide decreased tetanic [Ca(2+)](i) by ≈25 %, but had no significant effect on the rate of SR Ca(2+) uptake or the force-[Ca(2+)](i) relationship. Repeated tetanic stimulation resulted in increased tetanic [Ca(2+)](i), and this increase was smaller after CaMKII inhibition. In conclusion, CaMKII-induced phosphorylation facilitates SR Ca(2+) release in the basal state and during repeated contractions, providing a positive feedback between [Ca(2+)](i) and SR Ca(2+) release.